ANALISIS KOMODIFIKASI KONTRIBUTOR DALAM PRODUKSI BERITA TELEVISI - Yoedtadi, Moehammad Gafar; Loisa, Riris; Sukendro, Genep; Oktavianti, Roswita; Utami, Lusia Savitri Setyo (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
The pattern of news production in the Indonesian television broadcasting industry generally uses two human resources, namely permanent journalists and temporary journalists. Regular journalists are organic employees of television companies. Meanwhile, journalists who are not permanent or contributors only work under a news sale and purchase contract. They are not the organic employees of the television company. They only get honorarium when the news airs. As a result of such a working relationship, the contributors' bargaining position is very weak in front of the television station management. The coverage and news agenda will follow the tastes of television stations. News coverage that is at risk of not airing will be avoided. As a result, there has been neglect of the ideal function of the media in serving the public interest. Based on the political economy theory of media, there has been a commodification of labor in the television news production process.  The object of this research is the process of commodification of contributors in the production of television news.Meanwhile, the subjects of this study were television contributors, and news producers of Jakarta television stations.Other contributors who became research informants were in West Java and Ambon. This research uses a qualitative approach with a case study method. Collecting data using in-depth interviews, observation and literature study. The results showed that there has been a commodification of contributors in the production of television news. Television management exploits contributors. Television management promotes false consciousness among contributors who are unaware of the commodification. Pola produksi berita pada industri penyiaran televisi Indonesia umumnya memanfaatkan dua sumber daya manusia, yakni jurnalis tetap dan jurnalis lepas. Jurnalis tetap adalah karyawan organik dari perusahaan televisi. Sementara jurnalis lepas atau kontributor hanya bekerja berdasarkan kontrak jual beli berita. Mereka bukan karyawan organik perusahaan televisi. Mereka hanya mendapat imbalan honor ketika beritanya ditayangkan. Akibat dari hubungan kerja semacam itu, posisi tawar kontributor sangat lemah dihadapan manajemen stasiun televisi. Agenda peliputan dan berita akan mengikuti selera stasiun televisi. Peliputan berita yang berisiko tidak tayang akan dihindari. Akibatnya terjadi pengabaian fungsi ideal media dalam melayani kepentingan publik. Makalah ini hendak membedah proses komodifikasi kontributor berdasarkan teori ekonomi politik media. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Objek dari penelitian ini adalah proses komodifikasi kontributor dalam produksi berita televisi. Sementara itu subjek dari penelitian ini adalah para kontributor televisi, dan para produser berita stasiun televisi Jakarta. Kontributor lain yang menjadi informan penelitian berada di wilayah Jawa Barat dan Ambon. Pengumpulan data dengan menggunakan wawancara mendalam, observasi dan studi literatur. Hasil penelitian menunjukkan telah terjadi komodifikasi kontributor dalam produksi berita televisi. Manajemen televisi melakukan eksploitasi tenaga kontributor. Manajemen televisi mempromosikan kesadaran palsu kepada para kontributor sehingga tidak menyadari adanya komodifikasi tersebut.